Tracking consolidation of out-of-autoclave prepreg corners using pressure sensors. (December 2022) - Maes, Vincent K.; Radhakrishnan, Arjun; Hartley, Jamie; Sykes, Stuart; Kratz, James
Abstract: A total of eight corner pieces with the four different thickness-to-radius ratio, one set using external and one set using internal tooling, were made to identify how unidirectional carbon-epoxy prepreg layers consolidate during lay-up and oven vacuum bag moulding. Flexible thin-film pressure sensors were introduced to both internal and external corner mould surfaces and pressure measurements were taken during hand lay-up. A second sensor was added to monitor how the pressure gradient changes during oven vacuum bag moulding. Time-lapsed pressure measurements found that the geometry-induced excess pressure on the external corners decreases during moulding, leading to some corner thinning but this effect is small. Meanwhile, internal corner parts saw significant ply-bridging in high thickness-to-radius conditions that could not be resolved during consolidation, resulting in corner thickening and voids. The flexible sensors are a viable option for in-situ pressure monitoring for potential meso -structural defects during composite product development or manufacture.